2004
DOI: 10.1111/j.1742-1241.2004.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of telmisartan vs. losartan in control of mild-to-moderate hypertension: a multicentre, randomised, double-blind study

Abstract: This multicentre, randomised, double-blind, doubledummy, parallel-group study compared the efficacy and safety of telmisartan with those of losartan after 8 weeks' treatment. In total, 330 patients with mild-tomoderate hypertension (systolic blood pressure [SBP] <180 mmHg; diastolic blood pressure [DBP] 95-109 mmHg) were randomly assigned to receive oncedaily treatment with telmisartan 40 mg (n ¼ 164) or losartan 50 mg (n ¼ 166). After 4 weeks' treatment, if a patient's DBP was ‡90 mmHg, the dose was increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 12 publications
0
19
0
3
Order By: Relevance
“…A total of 11 randomized controlled trials met the criteria for inclusion in this meta-analysis. [13][14][15][16][17][18][19][20][21][22][23] The flow of the studies included in our analysis is shown in Figure 1. In one trial, 13 in which patients were randomized to receive telmisartan 40 mg, telmisartan 80 mg, losartan 50 mg, or placebo, we did not extract the data of telmisartan 80 mg group so as to avoid potential duplication.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 11 randomized controlled trials met the criteria for inclusion in this meta-analysis. [13][14][15][16][17][18][19][20][21][22][23] The flow of the studies included in our analysis is shown in Figure 1. In one trial, 13 in which patients were randomized to receive telmisartan 40 mg, telmisartan 80 mg, losartan 50 mg, or placebo, we did not extract the data of telmisartan 80 mg group so as to avoid potential duplication.…”
Section: Resultsmentioning
confidence: 99%
“…Zhu JR et al and Mallion J et al showed that telmisartan was more effective than losartan in hypertensive patients. 13,14 Mini mental status examination test and trail making test part-A are standard test for evaluation of cognitive impairment. An increase in the MMSE score and reduction in TMT part-A score are used as marker of improvement in cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] The efficacy of telmisartan has been shown to be at least equivalent to that of many other commonly prescribed antihypertensive agents (eg, losartan, enalapril, and amlodipine). [15][16][17][18] Data regarding the influence of telmisartan on endothelial function and RVRI in patients with essential hypertension remain scarce. Therefore the aim of this study was to examine whether telmisartan, the calcium channel blocker nisoldipine, or the combination of both drugs improves endothelial function and renal vascular resistance in patients with essential hypertension.…”
Section: Introductionmentioning
confidence: 99%